Balancing Act: Cadet Adaptation in the Port & Shipping Management Study Program at Sekolah Tinggi Ilmu Pelayaran (STIP) Jakarta - Simanjuntak, Marudut Bernadtua; Ala, Asman; Simanjuntak, Ronald; Hamidi, Nazilul; Sihombing, Derma Watty (Innovative: Journal Of Social Science Research, 2023)
This research paper delves into the intricate process of adaptation undertaken by cadets enrolled in the Port & Shipping Management Study Program at Sekolah Tinggi Ilmu Pelayaran (STIP) Jakarta. These cadets are subject to a rigorous Maritime Education and Boarding Learning System, which combines elements of semi-military and fully vocational training to prepare them for maritime industry roles, with a particular emphasis on the Port and Shipping sector. Employing a descriptive qualitative methodology, this study aims to unravel the strategies and challenges faced by cadets as they strive to maintain a delicate balance between the demanding aspects of their daily life. This equilibrium includes the rigorous academic commitments of the Port & Shipping Management Program, the disciplined and structured lifestyle imposed by the Maritime Education and Boarding Learning System, and the imperative of cultivating a smart approach to their studies. Through a thorough examination of the cadets' experiences, as conveyed through interviews and document analysis, this research paper aims to elucidate the psychological and behavioural intricacies of cadet life. It explores how they navigate through the challenges, adapt to the demanding environment, and ultimately prepare themselves for fulfilling careers within the maritime industry. The findings of this study will provide valuable insights into the educational and psychological dynamics involved in cadet adaptation. These insights may have significant implications for improving the curriculum, support systems, and overall quality of education provided in the Port & Shipping Management Study Program at STIP Jakarta.